Wear-resistant strengthening process for light titanium alloy gear

Through the synergistic process of specific components of titanium alloy rods and hardened layers, the early failure problem of titanium alloy gears in high load and high temperature environments is solved, which significantly improves its fatigue and wear resistance and meets the high-performance needs of high-temperature meshing surfaces.

CN119550005AActive Publication Date: 2025-03-04SHAANXI ZHENMING NEW MATERIAL TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510121471.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-03-04
Estimated Expiration
2045-01-26

AI Technical Summary

Technical Problem

Existing titanium alloy gears have the risk of early failure under high load cycles and high temperature environments, and their fatigue resistance is not sufficient to meet the requirements of high-temperature meshing surfaces.

Method used

Titanium alloy rods with specific components are used, and the hardness and fatigue performance of the material are improved through high-temperature crystallization, low-temperature annealing, solid solution treatment and aging treatment. At the same time, a hardened layer of 2-4μm thick is formed on the surface of the gear to enhance its wear resistance and contact fatigue performance.

Benefits of technology

It significantly improves the fatigue resistance and wear resistance of titanium alloy gears at room temperature and high temperature, extends its service life, and meets the high performance requirements of high-temperature meshing surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a light titanium alloy gear wear-resistant strengthening process, and belongs to the technical field of titanium alloy gears, and the light titanium alloy gear wear-resistant strengthening process comprises the following steps: (1) preparing a titanium alloy bar which comprises the following components in percentage by weight: 4.5%-5.8% of Al, 3.2%-4.7% of Cr, 1.4%-2.7% of Mo, 1.8%-2.6% of Zr, 2.3%-3.9% of V, 0.11%-0.19% of Si, 1.8%-2.7% of La, 0.12%-0.25% of Fe and the balance of Ti and inevitable impurities; (2) roughly machining the titanium alloy bar into a gear blank; (3) the gear blank is subjected to hot isostatic pressing treatment, and then a hardened layer is formed on the surface of the gear blank through fusion covering; and (4) the titanium alloy gear with the hardened layer is machined to the designed size, and the titanium alloy gear is obtained. The prepared titanium alloy gear is excellent in wear resistance, corrosion resistance and contact fatigue performance and good in temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium alloy gears, and in particular relates to a wear-resistant strengthening process for lightweight titanium alloy gears. Background Art

[0002] Gears have always been important basic components in the machinery industry because of their advantages of large power transmission range, high transmission efficiency, accurate transmission ratio, long service life, and reliable operation. Titanium alloy gears are a special type of gear made of titanium and its alloy materials. They are designed and manufactured to meet the needs of specific applications, especially in environments that require light weight, high strength, corrosion resistance, and high temperature resistance.

[0003] However, in the face of some special working conditions, most titanium alloys cannot meet the increasingly high requirements of use. For example, the gears used in helicopter transmission systems are subjected to alternating loads and severe impact loads. The working environment includes various alternating stresses, impact dynamic stresses, wear, corrosion, etc. Although titanium alloys have good fatigue strength, there may still be a risk of early failure under high load cycles. Moreover, with the advancement of design, the increase in energy and speed, the temperature of the gear meshing surface is also increasing, and the gear meshing surface temperature can be as high as 300°C. The fatigue resistance of titanium alloy gears on the market at high temperatures cannot meet the market requirements.

[0004] Therefore, there is an urgent need for a lightweight titanium alloy gear wear-resistant strengthening process. Summary of the invention

[0005] The purpose of the present invention is to provide a wear-resistant strengthening process for lightweight titanium alloy gears.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: A lightweight titanium alloy gear wear-resistant strengthening process comprises the following steps: (1) Preparing a titanium alloy rod, comprising the following steps: Step 1: The titanium alloy rod comprises the following components in weight percentage: Al 4.5%-5.8%, Cr 3.2%-4.7%, Mo 1.4%-2.7%, Zr 1.8%-2.6%, V 2.3%-3.9%, Si 0.11%-0.19%, La 1.8%-2.7%, Fe 0.12-0.25%, and the rest is Ti and unavoidable impurities; the components of the titanium alloy rod are mixed evenly and then pressed to obtain an electrode block; Step 2: melting the electrode block in a vacuum consumable furnace to obtain a titanium alloy blank; Step 3, forging the titanium alloy billet at 1000° C.-1150° C., and then placing it in a fine forging machine and forging it at 900° C.-980° C. to obtain a forged titanium alloy bar; Step 4: crystallizing and annealing the forged titanium alloy rod in sequence to obtain a semi-finished titanium alloy rod; Step 5, subjecting the semi-finished titanium alloy rod to solution treatment and aging treatment in sequence, and then air cooling to room temperature to obtain a titanium alloy rod; (2) Rough processing of titanium alloy bars into gear blanks; (3) The gear blank is subjected to hot isostatic pressing treatment, TiC powder, Ti powder and Ni powder are mixed in a ratio of 1: (1.4-1.7): (0.2-0.6), and a 2-4 μm thick hardened layer is formed on the surface of the gear blank at a power of 2200-2300 W and a scanning speed of 3.0-3.3 mm / s to obtain a titanium alloy gear with a hardened layer; (4) The titanium alloy gear with the hardened layer is processed to a designed size to obtain a titanium alloy gear.

[0007] Further, the weight percentage of Al is less than the sum of the weight percentages of Cr and Mo.

[0008] The present invention uses a titanium alloy rod of a specific component and a titanium alloy gear prepared in synergy with a hardened layer, and finds that when the weight percentage of Al is less than the sum of the weight percentages of Cr and Mo, the contact fatigue resistance of the titanium alloy gear at room temperature can be improved under this condition. . Elements such as Al, Cr, and Mo can form different phase structures in the titanium matrix. Al usually promotes the formation of the α phase (close-packed hexagonal structure), while Cr and Mo tend to increase the stability of the β phase (body-centered cubic structure). Controlling the ratio of these two phases helps to optimize the room-temperature fatigue resistance of the material; however, the contact fatigue performance of the titanium alloy gear under this condition is not ideal.

[0009] Furthermore, the weight ratio of Al, Cr and Zr is (5.0-5.4):(3.2-3.8):(2.0-2.5).

[0010] Since the gear transmission system needs to withstand high stress, contact fatigue performance is a very important indicator. Contact fatigue refers to the phenomenon that cracks appear on the surface or near-surface area of ​​the material under repeated stress and gradually expand, eventually leading to material failure. Through a large number of experiments, it is found that the contact fatigue performance of titanium alloy gears at high temperatures can be improved when Al, Cr, and Zr are in a specific ratio. Analysis shows that Al is an α-phase stabilizing element and can promote the formation of α-phase. An appropriate amount of Al can enhance the hardness and strength of titanium alloys, but excessive amounts will lead to increased brittleness; Cr and Zr are also α-phase stabilizing elements, which can refine grains, improve the toughness of materials, and also improve the oxidation resistance and corrosion resistance of materials. Al, Cr, and Zr can all improve the strength of titanium alloys through a solid solution strengthening mechanism. They can form fine and dispersed strengthening phases, such as TiAl, TiCr, and TiZr compounds, which are distributed in the matrix and increase the deformation resistance of materials at high temperatures. When the ratio of Al, Cr, and Zr is appropriate, the interface characteristics of the α / β phase interval can be optimized, interface defects can be reduced, and thus the fatigue life of the material can be improved.

[0011] Furthermore, the titanium alloy rod includes the following components in weight percentage: Al 5.2%, Cr 3.3%, Mo 2.4%, Zr 2.4%, V 3.1%, Si 0.15%, La 2.4%, Fe 0.18%, and the rest is Ti and inevitable impurities.

[0012] Furthermore, the smelting process is as follows: placing the electrode block in a vacuum consumable furnace for smelting, heating the temperature to 1650°C-1670°C at a heating power of 12kW / min-14kW / min, keeping the temperature for 20min-25min, and naturally cooling for 2-3h to obtain a titanium alloy billet.

[0013] Furthermore, the crystallization method is: heating to 950°C-980°C and then keeping warm for 5h-7h.

[0014] Furthermore, the annealing method is: heating to 600°C-620°C and then keeping warm for 5h-7h.

[0015] The present invention sequentially performs high temperature crystallization and low temperature annealing on the forged titanium alloy rod, and this series of heat treatment processes can improve the hardness of the titanium alloy. High temperature crystallization can promote the uniform distribution of alloy elements in the entire matrix, eliminating the component segregation phenomenon that may occur during casting or forging. In the low temperature annealing stage, second phase particles (such as TiAl, TiCr, etc.) precipitated from the solid solution will form inside the material, and these small and evenly distributed particles can play a strengthening role and improve the hardness of the material.

[0016] Furthermore, the solution treatment method is: keeping the temperature at 750°C-780°C for 30min-60min.

[0017] Furthermore, the aging treatment method is: after the solution treatment, the alloy is naturally cooled to 520°C-560°C in the furnace and kept at this temperature for 4h-6h.

[0018] Furthermore, the conditions of the hot isostatic pressing are: maximum pressure of 180-200 MPa, pressure increase rate of 20-30 MPa / min, and holding time of 2-4 min.

[0019] Furthermore, the preparation of the titanium alloy rod also includes the following steps: subjecting the semi-finished titanium alloy rod to solution treatment and aging treatment in sequence, then air cooling to room temperature, and applying a laser-sprayed TiN coating on the surface with a thickness of 5-20 μm.

[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The titanium alloy gear prepared by the present invention through the synergistic effect of titanium alloy bars of specific components and hardened layers has excellent wear resistance and good contact fatigue resistance.

[0021] 2. The present invention adjusts the alloy composition. When the weight percentage of Al is less than the sum of the weight percentages of Cr and Mo, the fatigue resistance of the titanium alloy gear at room temperature can be improved under this condition.

[0022] 3. The present invention can improve the contact fatigue performance of titanium alloy gears at high temperatures when Al, Cr and Zr are in specific proportions.

[0023] 4. The present invention sequentially subjects the forged titanium alloy rod to high temperature crystallization and low temperature annealing treatments. This series of heat treatment processes can improve the hardness of the titanium alloy. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] This embodiment provides a lightweight titanium alloy gear wear-resistant strengthening process, comprising the following steps: (1) Preparing a titanium alloy rod, comprising the following steps: Step 1: The titanium alloy rod comprises the following components in weight percentage: Al 5.2%, Cr 3.3%, Mo 2.4%, Zr 2.4%, V 3.1%, Si 0.15%, La 2.4%, Fe 0.18%, and the rest is Ti and unavoidable impurities; the components of the titanium alloy rod are mixed evenly and then pressed to obtain an electrode block; Step 2: Melting the electrode block in a vacuum consumable furnace, placing the electrode block in a vacuum consumable furnace, heating it to 1660° C. at a heating power of 13 kW / min, keeping the temperature for 22 minutes, and naturally cooling it for 2.5 hours to obtain a titanium alloy billet; Step 3, forging the titanium alloy billet at 1080° C. for 2 minutes, then placing it in a fine forging machine and forging it at 920° C. for 5 minutes to obtain a forged titanium alloy bar; Step 4: The forged titanium alloy rod is subjected to high temperature crystallization in sequence: heating to 960°C and then keeping the temperature for 6 hours; and then low temperature annealing: heating to 610°C and then keeping the temperature for 6 hours to obtain a semi-finished titanium alloy rod; Step 5: firstly subject the semi-finished titanium alloy rod to a solution treatment, and the conditions of the solution treatment are: keeping the temperature at 770°C for 40 minutes; then naturally cooling to 540°C with the furnace and keeping the temperature for 5 hours for aging treatment, and then air cooling to room temperature to obtain a titanium alloy rod; (2) Rough processing of titanium alloy bars into gear blanks; (3) The gear blank was subjected to hot isostatic pressing treatment with a pressure increase rate of 25 MPa / min, a maximum pressure of 190 MPa, and a holding time of 3 min at the maximum pressure. TiC powder, Ti powder, and Ni powder in a weight ratio of 1:1.5:0.4 were mixed, and a 3 μm thick hardened layer was formed on the surface of the gear blank at a power of 2250 W and a scanning speed of 3.2 mm / s to obtain a titanium alloy gear with a hardened layer. The particle size of the TiC powder was 200-300 nm, purchased from Nianzhong Keyannuo (Beijing) Technology Co., Ltd., item number: BM11316; the particle size of the Ti powder was 400-500 nm, purchased from Nianzhong Keyannuo (Beijing) Technology Co., Ltd.; the particle size of the Ni powder was 700-800 nm, purchased from Nianzhong Keyannuo (Beijing) Technology Co., Ltd.

[0027] (4) The titanium alloy gear with the hardened layer is processed to a designed size to obtain a titanium alloy gear.

[0028] Example 2

[0029] This embodiment provides a lightweight titanium alloy gear wear-resistant strengthening process, comprising the following steps: (1) Preparing a titanium alloy rod, comprising the following steps: Step 1: The titanium alloy rod comprises the following components in weight percentage: Al 5.0%, Cr 3.2%, Mo 2.7%, Zr 2.0%, V 2.3%, Si 0.11%, La 1.8%, Fe 0.12%, and the rest is Ti and inevitable impurities; the components of the titanium alloy rod are mixed evenly and then pressed to obtain an electrode block; Step 2: Melting the electrode block in a vacuum consumable furnace, placing the electrode block in a vacuum consumable furnace, heating it to 1650° C. at a heating power of 12 kW / min, keeping the temperature for 20 minutes, and naturally cooling it for 2 hours to obtain a titanium alloy billet; Step 3, forging the titanium alloy billet at 1000° C. for 2 min, then placing it in a fine forging machine and forging it at 900° C. for 5 min to obtain a forged titanium alloy bar; Step 4: The forged titanium alloy rod is subjected to high temperature crystallization in sequence: heating to 950°C and then keeping the temperature for 5 hours; and then low temperature annealing: heating to 600°C and then keeping the temperature for 5 hours to obtain a semi-finished titanium alloy rod; Step 5: firstly subject the semi-finished titanium alloy rod to a solution treatment, and the conditions of the solution treatment are: keeping the temperature at 750°C for 30 minutes; then naturally cooling to 520°C and keeping the temperature for 4 hours for aging treatment, and then air cooling to room temperature to obtain a titanium alloy rod; (2) Rough processing of titanium alloy bars into gear blanks; (3) The gear blank was subjected to hot isostatic pressing treatment with a pressure increase rate of 20 MPa / min, a maximum pressure of 180 MPa, and a holding time of 2 min at the maximum pressure. TiC powder, Ti powder, and Ni powder in a weight ratio of 1:1.4:0.2 were mixed, and a 3 μm thick hardened layer was formed on the surface of the gear blank at a power of 2200 W and a scanning speed of 3.0 mm / s to obtain a titanium alloy gear with a hardened layer. The particle size of the TiC powder was 200-300 nm, purchased from Nianzhong Keyannuo (Beijing) Technology Co., Ltd., item number: BM11316; the particle size of the Ti powder was 400-500 nm, purchased from Nianzhong Keyannuo (Beijing) Technology Co., Ltd.; the particle size of the Ni powder was 700-800 nm, purchased from Nianzhong Keyannuo (Beijing) Technology Co., Ltd.

[0030] (4) The titanium alloy gear with the hardened layer is processed to a designed size to obtain a titanium alloy gear.

[0031] Example 3

[0032] This embodiment provides a lightweight titanium alloy gear wear-resistant strengthening process, comprising the following steps: (1) Preparing a titanium alloy rod, comprising the following steps: Step 1: The titanium alloy rod comprises the following components in weight percentage: Al 5.4%, Cr 3.8%, Mo 1.9%, Zr 2.5%, V 3.9%, Si 0.19%, La 2.7%, Fe 0.25%, and the rest is Ti and inevitable impurities; the components of the titanium alloy rod are mixed evenly and then pressed to obtain an electrode block; Step 2: Melting the electrode block in a vacuum consumable furnace, placing the electrode block in a vacuum consumable furnace, heating it to 1670° C. at a heating power of 14 kW / min, keeping the temperature for 25 minutes, and naturally cooling it for 3 hours to obtain a titanium alloy billet; Step 3, forging the titanium alloy billet at 1150° C. for 2 minutes, then placing it in a fine forging machine and forging it at 980° C. for 5 minutes to obtain a forged titanium alloy bar; Step 4: The forged titanium alloy rod is subjected to high temperature crystallization in sequence: heating to 980°C and then keeping the temperature for 7 hours; and then low temperature annealing: heating to 620°C and then keeping the temperature for 7 hours to obtain a semi-finished titanium alloy rod; Step 5: firstly subject the semi-finished titanium alloy rod to a solution treatment, and the conditions of the solution treatment are: keeping the temperature at 780°C for 60 minutes; then naturally cooling to 560°C and keeping the temperature for 6 hours for aging treatment, and then air cooling to room temperature to obtain a titanium alloy rod; (2) Rough processing of titanium alloy bars into gear blanks; (3) The gear blank was subjected to hot isostatic pressing treatment with a pressure increase rate of 30 MPa / min, a maximum pressure of 200 MPa, and a holding time of 4 min at the maximum pressure. TiC powder, Ti powder, and Ni powder in a weight ratio of 1:1.7:0.6 were mixed, and a 3 μm thick hardened layer was formed on the surface of the gear blank at a power of 2300 W and a scanning speed of 3.3 mm / s to obtain a titanium alloy gear with a hardened layer. The particle size of the TiC powder was 200-300 nm, purchased from Nianzhong Keyannuo (Beijing) Technology Co., Ltd., item number: BM11316; the particle size of the Ti powder was 400-500 nm, purchased from Nianzhong Keyannuo (Beijing) Technology Co., Ltd.; the particle size of the Ni powder was 700-800 nm, purchased from Nianzhong Keyannuo (Beijing) Technology Co., Ltd.

[0033] (4) The titanium alloy gear with the hardened layer is processed to a designed size to obtain a titanium alloy gear.

[0034] Comparative Example 1 The difference between this comparative example and Example 1 is that the titanium alloy rod includes the following components in weight percentage: Al4.0%, Cr3.0%, Mo3.4%, Zr2.9%, V2.1%, Si0.25%, La3.4%, Fe0.08%, and the rest is Ti and unavoidable impurities.

[0035] Comparative Example 2 The difference between this comparative example and Example 1 is that the titanium alloy rod includes the following components in weight percentage: Al 5.8%, Cr 3.2%, Mo 1.4%, Zr 2.4%, V 3.1%, Si 0.15%, La 2.4%, Fe 0.18%, and the rest is Ti and unavoidable impurities.

[0036] Comparative Example 3 The difference between this comparative example and Example 1 is that the titanium alloy rod includes the following components in weight percentage: Al4.5%, Cr3.8%, Mo2.4%, Zr2.6%, V3.1%, Si0.15%, La2.4%, Fe0.18%, and the rest is Ti and unavoidable impurities.

[0037] Comparative Example 4 The difference between this comparative example and Example 1 is as follows: Step 4, the forged titanium alloy rod is sequentially subjected to high-temperature crystallization, heated to 760°C and then kept warm for 10 hours; then low-temperature annealing, heated to 660°C and then kept warm for 4 hours, to obtain a semi-finished titanium alloy rod.

[0038] Comparative Example 5 The difference between this comparative example and Example 1 is as follows: Step 5, the semi-finished titanium alloy rod is first subjected to a solution treatment, and the conditions for the solution treatment are: keeping warm at 800°C for 20 minutes; then naturally cooling to 500°C with the furnace and keeping warm for 7 hours for aging treatment, and then air cooling to room temperature to obtain a titanium alloy rod.

[0039] Comparative Example 6 The difference between this comparative example and Example 1 is as follows: (3) the gear blank is subjected to hot isostatic pressing treatment, with a pressure increase rate of 45 MPa / min, a maximum pressure of 170 MPa, and a holding time of 2 min at the maximum pressure to obtain a gear blank.

[0040] Comparative Example 7 The difference between this comparative example and Example 1 is that TiC powder, Ti powder and Ni powder are mixed in a ratio of 1:1:1.

[0041] Performance Testing The performance of the titanium alloy gears prepared in Examples 1-3 of the present invention and Comparative Examples 1-7 was tested, and the specific testing method was as follows: 1. Hardness is tested in accordance with GB / T4340.1-2009 "Vickers hardness test for metallic materials - Part 1: Test method".

[0042] 2. Wear performance is tested in accordance with GB / T12444-2006 "Metallic material wear test method - Test ring-test block sliding wear test" standard.

[0043] 3. The contact fatigue performance is tested in accordance with GB / T14229-1993 "Gear Contact Fatigue Strength Test Method".

[0044] The test results are shown in Table 1.

[0045] Table 1 Performance test results of titanium alloy gears

[0046] It can be seen from the above performance test results that the titanium alloy gears of Examples 1-3 have high hardness, good wear resistance and fatigue resistance, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect of the specific component ratio of the titanium alloy rod, the ratio of the hardened layer components and the strengthening process of the titanium alloy gear.

[0047] However, the comparative examples did not adopt the necessary technical solutions, resulting in that their corresponding performance tests were significantly worse than those of the embodiments. In comparative example 1, the component ratio of the titanium alloy rod was changed, and it can be seen that the performance of the titanium alloy at room temperature and high temperature decreased. In comparative example 2, when the weight percentage of Al was greater than the sum of the weight percentages of Cr and Mo, it can be seen from the results that the contact fatigue limit at room temperature was affected. In comparative example 3, the ratios of Al, Cr and Zr were different, and it can be seen from the results that the fatigue resistance at high temperature decreased. Comparative examples 4-6 changed the processing conditions of the titanium alloy gears, and it can be seen from the results that the comprehensive performance of the titanium alloy gears was affected. In comparative example 7, the component ratios used for the hardening layer cladding were different, and it can be seen from the results that the wear resistance of the titanium alloy gears decreased, indicating that there is a synergistic effect between the components of the hardening layer and the components of the aluminum alloy rod, which jointly improve the wear resistance of the titanium alloy gears. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0048] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A lightweight titanium alloy gear wear-resistant strengthening process, characterized in that: The following steps are involved: (1) Preparing a titanium alloy rod, comprising the following steps: Step 1: The titanium alloy rod comprises the following components in weight percentage: Al 4.5%-5.8%, Cr 3.2%-4.7%, Mo 1.4%-2.7%, Zr 1.8%-2.6%, V 2.3%-3.9%, Si 0.11%-0.19%, La 1.8%-2.7%, Fe 0.12-0.25%, and the rest is Ti and unavoidable impurities; the components of the titanium alloy rod are mixed evenly and then pressed to obtain an electrode block; Step 2: melting the electrode block in a vacuum consumable furnace to obtain a titanium alloy blank; Step 3, forging the titanium alloy billet at 1000° C.-1150° C., and then placing it in a fine forging machine and forging it at 900° C.-980° C. to obtain a forged titanium alloy bar; Step 4: crystallizing and annealing the forged titanium alloy rod in sequence to obtain a semi-finished titanium alloy rod; Step 5, subjecting the semi-finished titanium alloy rod to solution treatment and aging treatment in sequence, and then air cooling to room temperature to obtain a titanium alloy rod; (2) Rough processing of titanium alloy bars into gear blanks; (3) The gear blank is subjected to hot isostatic pressing treatment, TiC powder, Ti powder and Ni powder in a weight ratio of 1: (1.4-1.7): (0.2-0.6) are mixed, and a 2-4 μm thick hardened layer is formed on the surface of the gear blank at a power of 2200-2300 W and a scanning speed of 3.0-3.3 mm / s to obtain a titanium alloy gear with a hardened layer; (4) The titanium alloy gear with the hardened layer is processed to a designed size to obtain a titanium alloy gear.

2. The wear-resistant strengthening process for lightweight titanium alloy gears according to claim 1 is characterized in that: The weight percentage of Al is less than the sum of the weight percentages of Cr and Mo.

3. The wear-resistant strengthening process for lightweight titanium alloy gears according to claim 2 is characterized in that: The weight ratio of Al, Cr and Zr is (5.0-5.4):(3.2-3.8):(2.0-2.5).

4. The wear-resistant strengthening process for lightweight titanium alloy gears according to claim 3 is characterized in that: The titanium alloy rod includes the following components in weight percentage: Al 5.2%, Cr 3.3%, Mo 2.4%, Zr 2.4%, V 3.1%, Si 0.15%, La 2.4%, Fe 0.18%, and the rest is Ti and inevitable impurities.

5. The wear-resistant strengthening process for lightweight titanium alloy gears according to claim 1 is characterized in that: The smelting process is as follows: placing the electrode block in a vacuum consumable furnace for smelting, heating the temperature to 1650°C-1670°C at a heating power of 12kW / min-14kW / min, keeping the temperature for 20min-25min, and naturally cooling for 2-3h to obtain a titanium alloy billet.

6. The wear-resistant strengthening process for lightweight titanium alloy gears according to claim 1 is characterized in that: The crystallization method is: heating to 950° C.-980° C. and then keeping the temperature for 5 h-7 h.

7. The wear-resistant strengthening process for lightweight titanium alloy gears according to claim 1 is characterized in that: The annealing method is: heating to 600° C.-620° C. and then keeping the temperature for 5 h-7 h.

8. The wear-resistant strengthening process for lightweight titanium alloy gears according to claim 1 is characterized in that: The method of the solution treatment is: keeping the temperature at 750°C-780°C for 30min-60min; the method of the aging treatment is: cooling naturally to 520°C-560°C with the furnace after the solution treatment and keeping the temperature for 4h-6h.

9. The wear-resistant strengthening process for lightweight titanium alloy gears according to claim 1 is characterized in that: The conditions of the hot isostatic pressing are: maximum pressure of 180-200 MPa, pressure increase rate of 20-30 MPa / min, and pressure holding time of 2-4 min.

10. The wear-resistant strengthening process for lightweight titanium alloy gears according to claim 1, characterized in that: The preparation of the titanium alloy rod also includes the following steps: subjecting the semi-finished titanium alloy rod to solution treatment and aging treatment in sequence, then air cooling to room temperature, and applying a laser sprayed TiN coating on the surface with a thickness of 5-20 μm.

Citation Information

Patent Citations

  • Titanium alloy gear and preparation method thereof

    CN107893228A

  • Titanium alloy gear and preparation method thereof

    CN109295343A

  • Preparation method of high-strength titanium alloy bar for additional material manufacturing powder

    CN112080656A

  • Ti / Al composite wire for additive manufacturing of TiAl alloy and preparation method of Ti / Al composite wire

    CN113523643A

  • Method for rapidly preparing titanium nitride coating on surface of titanium alloy through ultra-low power laser

    CN115386825A